Study on the Historical and Cultural Overview of Northern Shaanxi Based on Music Folk Customs and Agriculture and Animal Husbandry Folk Customs - Xiang, Xiao (Transactions on Social Science, Education and Humanities Research, 2023)
North Shaanxi is located near the ancient historical center of China, Chang’an, and is a military stronghold. It is also the border between the farming and grassland ethnic groups in the Central Plains, and has rich research value. This article first explores the music and folk culture of northern Shaanxi from three aspects: folk songs, Nao Yangge, and storytelling. As a way of expressing emotions among the people, music can best reflect the aspirations of the people of northern Shaanxi and plays an important role in studying the history and culture of northern Shaanxi. Subsequently, the agricultural and pastoral folk culture in northern Shaanxi will be introduced from both production and daily life. Regarding the production of agricultural and pastoral folk culture, this article studies from three dimensions: the agricultural and pastoral festival customs, sacrificial rituals, and belief customs of the people of northern Shaanxi. These three dimensions reflect the characteristics of the combination of agriculture and pastoral culture and the diversity of beliefs in northern Shaanxi. Regarding the daily life of agricultural and pastoral folk culture, with a focus on the catering culture and architectural characteristics of northern Shaanxi, it reflects the enthusiastic and heroic character of the people of northern Shaanxi from two aspects: food and housing. Music is the artistic embodiment of the people of northern Shaanxi, and agricultural and pastoral customs involve their historical origins, cultural characteristics, and local customs. Therefore, this article focuses on these two themes and presents the historical and cultural characteristics of northern Shaanxi from three perspectives: history, culture, and customs.